Type and Abundance of Phytoplankton in the Koto Tibun Reservoir, Kampar Regency, Riau Province - Rancelia Kristina Simanjuntak; Asmika H. Simarmata; Clemens Sihotang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Phytoplankton is a primary producer organism in aquatic ecosystem and it supplies oxygen to the waters through photosynthesis process. A research aim to determine types and abundance of phytoplankton in the Koto Tibun Reservoir has been carried out on February-March 2018. Sampling taken at three stations, namely Station 1 (riverine zone), Station 2 (transition zone) and Station 3 (lacustrin zone), once/week. Parameters measured were temperature, brightness, depth, pH, DO, CO2, nitrate (NO3) and phosphate (PO4). The types of phytoplankton found in the Koto Tibun Reservoir were 27 species that consist of 5 classes, namely Chlorophyceae (11 species), Baccillarophyceae (8 species), Zygnematophyceae (3 species), Cyanophyceae (4 species) and Euglenophyceae (1 species). The abundance of phytoplankton in Koto Tibun Reservoir ranges from 2,544-3,708 cells/ L. The water quality parameters were as follows:transparency 75.33-78.66 cm, temperatures 25.3-25.6 0C, pH 5, DO 4.78-5.62 mg / L, CO218.64-19.44 mg / L, phosphate 0.093-0.113 mg / L, nitrate 0.186-0.193 mg / L. Based on the abundance of phytoplankton, Koto Tibun Reservoir can be categorized as mesotrophic.Keyword: Phytoplankton, Water Quality Parameters, Koto Tibun Dam,Mesotrophic